Metode Pembelajaran Berbasis Proyek untuk Mereduksi Emosi Marah Anak Anger Tantrum Usia 4-5 Tahun di RA. Fatma Kec. Gondang Kab. Mojokerto: Project-Based Learning Method to Reduce Angry Emotions in Angry Tantrum Children Aged 4-5 Years in RA. Fatma District. Gondang District. Mojokerto - FADLILAH, FADLILAH; DWI BHAKTI INDRI (Jurnal Intelek Insan Cendikia, 2024)
Abstract Learning methods are one of the keys to the success of a learning process. Learning methods must also be adapted to the child's needs and conditions. A good learning method is a learning method that makes the child the center of learning while the teacher only becomes a facilitator. One child-centered learning method is the project-based learning method. The project-based learning method is a learning method that uses projects or activities as media. Students will be required to be more active and learning will feel very enjoyable with the projects or activities carried out. This research uses a project-based learning method to reduce angry emotions in children aged 4-5 years in RA. Fatma Ds. Pugeran District. Gondang District. Mojokerto. The aim of the research will be to examine: 1) The causes of anger tantrum behavior in children with the initial "A" shown in RA. Fatma Ds. Pugeran District. Gondang District. Mojokerto. 2) The application of project-based learning is implemented in RA. Fatma Ds. Pugeran District. Gondang District. Mojokerto. This research is a type of qualitative research where the results of data collection and data analysis show that project-based learning methods can be used to reduce angry emotions in children aged 4-5 years in RA. Apart from that, Fatma is also expected to foster enthusiasm for learning in class. Keywords: Project Based Learning Method, Anger Tantrum.